Enhancing Research Involvement of Young People With Lived Expertise: Reflecting on Experiences in Digital Mental Health Research - Josephine Brogden; Zsofi de Haan; Carla Gorban; Samuel J Hockey; Alexis Hutcheon; Frank Iorfino; Yun Ju C Song; Elizabeth Scott; Ian B Hickie; Sarah McKenna (JMIR Publications, 2024)
Given the rapid development of digital mental health technologies and a focus on connecting with youth, there is an urgent need to enhance the engagement of young people with lived expertise in research. Even so, youth with lived experience of accessing mental health services are particularly affected by power imbalances and may receive limited compensation in academic settings. Therefore, an emphasis on how research engagement not only improves the work but can benefit young people themselves is required. Here, 5 young people with lived expertise report on their experience of being employed as researchers at the University of Sydney's Brain and Mind Centre. As such, this team is uniquely placed to offer reflections from their work across multiple stages of research. This led to four key insights, including (1) creating accepting work cultures, (2) providing diverse opportunities for involvement, (3) giving young people agency and flexibility around sharing lived experiences, and (4) creating accommodating work environments for all researchers. We suggest that these insights can support more diverse ways of engaging young people and maximizing the value of participation for both researchers and young people themselves.